A Morphological Analysis of Derivational and Inflectional Morphemes in the ‘Life Today’ English Textbook for Grade 12 Students - Siti Nurul Hasanah; Tenia Ramalia; Nirna Nirmala (Learning Strategies: Jurnal Ilmu Pendidikan dan Pembelajaran, 2026)
This study aimed to analyze the types of bound morphemes, the processes and frequency of derivational and inflectional morphemes in the “Life Today” English textbook used by Grade 12 students in Indonesia to provide insights into morphological content presentation in EFL instructional materials. Morphological awareness is crucial for English as a Foreign Language learners’ vocabulary development and reading comprehension. Despite extensive research on morphological analysis in authentic texts, limited attention has been given to examining morphological content in educational materials. Understanding how morphemes are presented in textbooks is essential for optimizing English language instruction, particularly in Indonesia where English proficiency remains challenging. This research employed a descriptive qualitative design with document analysis to examine 22 reading texts across four units of the “Life Today” textbook. Using Fromkin, Rodman, and Hymas’s theoretical framework, the research systematically identified, categorized, and analyzed derivational and inflectional morphemes through a four-stage data collection process and Miles and Huberman’s three-stage data analytical framework. The analysis identified 1,409 morphological processes, with inflectional morphemes (1,096 words) significantly outnumbering derivational morphemes (313 words). All types morphological categories were present, including ten derivational processes and eight inflectional processes. The most frequent morpheme was plural (521 words) followed by past tense (259 words) and progressive (231 words). The predominance of inflectional morphemes validates theoretical predictions about their fundamental grammatical functions in English discourse. These findings provide evidence for morphological content optimization in EFL materials and support the integration of systematic morphological categories to enhance Indonesian students’ vocabulary development and communicative competence.